Association Between Maternal Mid-Upper Arm Circumference and Baby's Birth Weight (Majalah Kedokteran Bandung, 2022)
Birth weight can be a potential predictor for short-term and long-term health outcomes. Low birth weight can be an output from maternal malnutrition. Mothers' chronic energy malnutrition risk is detected by measuring maternal mid-upper arm circumference (MUAC). This study aimed to analyze the correlation of maternal MUAC with a baby's birth weight. This study was an analytic observational study that used secondary data from October 2021 to January 2022. Data were obtained from Tanjungsari Intergenerational Study Nutrition Working Group from 2014 to 2016. Subjects were 124 pairs of mother and baby who were recruited using total sampling. Data were analyzed using t-test and logistic regression. A significant association of maternal MUAC and the baby's birth weight (t (122) = 3.75, 95% CI 174.5, 564.0, p=0.000) was detected. Underweight (OR 23.3, 95% CI 2.6, 209.0, p=0.005), overweight, and obese (OR 0.05, 95% CI 0.01, 0.42, p=0.006) status was shown to have an association with MUAC. Education level and occupation status had no associations with MUAC. In conclusion, maternal MUAC is associated with baby's birth weight. The determinant factors of maternal MUAC were underweight, overweight, and obese status.
Keywords: birth weight; chronic energy malnutrition; MUAC; Tanjungsari